Effects of dietary licorice root (Glycyrrhriza glabra) supplementation, storage time and temperature on quality of quail eggs - Canoğulları Doğan, Sibel; Baylan, Mikail; Yaman, Sema; Bulancak, Ayşen (Progress in Nutrition, 2018)
This study was conducted to investigate the effect of licorice root (Glycyrrhriza glabra) supplementation, different storage temperature and storage time on egg quality in quails. Two hundred and forty 10-wk-old laying Japanese quails, randomly divided into four equal groups for dietary treatments, were fed using the commercial diet as a control group and the commercial diet supplemented with 0.5, 1.0 and 1.5% licorice root powder. The forty eggs were sampled and weighed for each one of storage time groups (i.e. 15, 30 and 45 days), and were stored at +4°C and +25°C. Egg internal and external quality characteristics were determined at the end of each storage period for each temperature. The egg albumen pH level was increased in a parallel of the escalation of storage time and temperature, whereas it was decreased as the licorice level was increased. Haugh Unit (HU) value was decreased with an increase of storage time and temperature, but it was increased in a parallel of accelerating level of licorice root. Though there were no significant differences in egg weight loss, yolk index and egg shell weight between the treatments, they were significant for the albumen index and egg shell thickness (P<0.05). Moreover, albumen index and egg shell thickness were increased with an enlarged licorice root supplementation. It was concluded that the use of licorice root in laying quail diet may be effective for the expansion of egg shelf life.